Evolution of Carbon Emissions and GDP Decoupling in Vietnam’s Electricity Sector - Chen, Chen; Inamdar, Mohammad Nizamuddin; Al-Odaini, Aiman (International Journal of Advanced AI Applications, 2025)
This study examines the key drivers of carbon emissions in Vietnam's electricity sector from 2002 to 2022 and investigates the evolving decoupling dynamics between economic growth and emissions. Employing the IPCC (2006) emission factor methodology for emissions estimation and the Tapio decoupling model to evaluate GDP-emissions elasticity, the analysis reveals a dramatic rise in emissions over the period, accelerating post-2010 amid 8-10% annual electricity demand growth. Coal's share in power generation escalated from 18% in 2005 to about 50% in 2020, fueling multiple-fold emission increases. The decoupling trajectory unfolds in three phases: expansive negative decoupling dominated 2001-2010, signaling carbon-intensive development; intermittent strong decoupling appeared in 2011-2015 despite coal's persistence; and sustained strong decoupling emerged in 2019-2022, driven by renewable energy surges and efficiency gains. These insights emphasize Vietnam's coal dependency while underscoring renewables' role in decoupling sustainability. Policy recommendations advocate expedited clean energy adoption, power mix restructuring, and reduced coal reliance to meet climate goals.